A Direct Enzymatic Assay for the Esterolytic Activity of Activated Hageman Factor - Ulevitch, Richard J; Letchford, David; Cochrane, C. G (Thrombosis and Haemostasis, 1974)
A direct enzymatic assay for activated Hageman factor (HFa) has been developed utilizing N-α-acetylgiycine lysine methyl ester (AGLME). This assay allowed the measurement of the esterolytic activity of purified Hageman factor (HF) which had been activated by enzymatic (trypsin) and non-enzymatic (kaolin) mechanisms. No esterolytic activity was detected in preparations of purified HF prior to activation.Studies with purified HF activated on kaolin demonstrated the following: (1) Simple saturation kinetics (Km = 9 mM, Turnover number = 2.5 min–1) at AGLME concentrations less than 0.04 M and substrate inhibition at AGLME concentrations greater than 0.04 M. (2) The substrate AGLME behaved as a competitive inhibitor of the activation of prekallikrein (PK) by HFa with an inhibition constant (Ki) of about 10 mM. (3) Both the esterolytic (AGLME hydrolysis) and the proteolytic activities (PK activation) were inhibited by diisopropylfluorosphosphate (DFP) with an approximate Ki of 5 × 10–4 M.